TP53 mutants and non-HPV16/18 genotypes are poor prognostic factors for concurrent chemoradiotherapy in locally advanced cervical cancer - Ikumi Kuno (Nature Portfolio, 2021)
Abstract Targeted sequencing for somatic mutations across the hotspots of 50 cancer-related genes was performed using biopsy specimens to investigate whether clinicopathological factors and genomic alterations correlated with prognosis in locally advanced cervical cancer. Seventy patients diagnosed with International Federation of Obstetrics and Gynecology (FIGO) stage III to IVA cervical cancer underwent radiotherapy or concurrent chemoradiotherapy at the National Cancer Center Hospital between January 2008 and December 2017. Mutations were detected in 47 of 70 [67% of cases; frequency of genetic alterations was as follows: PIK3CA (51%), FBXW7 (10%), PTEN (7.1%), and TP53 (5.7%)]. The Cancer Genome Atlas (TCGA) datasets showed a similar distribution of somatic mutations, but PIK3CA mutation frequency was significantly higher in our cohort than in TCGA datasets (P = 0.028). Patients with TP53 mutation were significantly related to poor progression-free survival (PFS) (hazard ratio [HR] = 3.53, P = 0.042). Patients with tumor diameters > 70 mm were associated with poor prognosis (HR = 2.96, P = 0.0048). Patients with non-HPV16/18 genotypes had worse prognosis than those with HPV16/18 genotypes (HR = 2.15, P = 0.030). Hence, patients with locally advanced cervical cancer, TP53 mutation, large tumor diameter, and non-HPV16/18 genotype were independently correlated with poor PFS, despite concurrent chemoradiotherapy.